Uji Kandungan Gizi Terhadap Beberapa Makanan Khas Kota Palopo - Adriani Adriani (Al-Kimia, 2015)
Purpose of this research is determine the value of the nutrients that are owned by traditional food such as kapurung, lawa and fish parede. This research can be used as reference material/information to the public about the nutritional content of the food three, thus increasing the value of consumption. In this research use several methods. Carbohydrate testing using Luff schrooll method, protein testing using Kjehdahl method and fat testing using Soxhletasi method. The results showed that the content of carbohydrates, proteins and fats for the cross beam is respectively 1.87%, 1.90 % and 35.30 %. For  Kapurung, carbohydrate levels of 1.77 % ,  0.99% protein and 0.48% fat. For fish Parede, 0.30 % carbohydrate, protein and fat by 15.66 % 1.05%. Lawa contains carbohydrate and high fat compared cross beam and fish Parede while the highest protein content owned by fish Parede.